2004
DOI: 10.1177/107424840400900107
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic and Proarrhythmic Properties of QT-Prolonging Antianginal Drugs

Abstract: In recent years there has been a major reorientation of drug therapy for cardiac arrhythmias, its changing role, and above all, a radical change in the class of arrhythmia drugs because of their impact on mortality. The decline in the use of sodium-channel blockers has led to an ex panding use of beta-blockers and simple or complex class III agents for controlling cardiac arrhythmias. Success with these agents in the context of their side effects has spurred the development of compounds with simpler ion-channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 56 publications
0
24
0
1
Order By: Relevance
“…Among the antiarrhythmic medications there are a variety of so-called pure class III antiarrhythmic agents, such as dofetilide or ibutilide, which, although effective in treating atrial fibrillation and flutter as well as ventricular tachyarrhythmias, are associated with sometimes fatal TdP, despite relatively modest increases in the QT interval. Conversely, the drug amiodarone, originally synthesized as an antianginal agent, has been associated with a negligibly low incidence of TdP, even though the drug can produce QT lengthening from 500 to 700 ms. 13 The reasons for this paradox are not entirely clear. Equally puzzling is the fact that not all drugs causing TdP are potent I-Kr blockers, and I-Kr block is not necessarily associated with TdP.…”
mentioning
confidence: 97%
“…Among the antiarrhythmic medications there are a variety of so-called pure class III antiarrhythmic agents, such as dofetilide or ibutilide, which, although effective in treating atrial fibrillation and flutter as well as ventricular tachyarrhythmias, are associated with sometimes fatal TdP, despite relatively modest increases in the QT interval. Conversely, the drug amiodarone, originally synthesized as an antianginal agent, has been associated with a negligibly low incidence of TdP, even though the drug can produce QT lengthening from 500 to 700 ms. 13 The reasons for this paradox are not entirely clear. Equally puzzling is the fact that not all drugs causing TdP are potent I-Kr blockers, and I-Kr block is not necessarily associated with TdP.…”
mentioning
confidence: 97%
“…On the flip side, the studies, although mostly limited to proof-of-concept, do highlight the potential utility of gene transfer in blunting ventricular arrhythmogenesis by overexpressing K ϩ channels (to accelerate repolarization), or blocking them selectively 23 to achieve focal class III 30 antiarrhythmic effects.…”
Section: Genetic Interventions To Influence Ventricular Repolarizationmentioning
confidence: 99%
“…There is also a risk of pharmacodynamic interactions with drugs that prolong the QT interval. 74 A recent study has shown that long-term therapy with ranolazine seems well tolerated in high-risk chronic stable angina patients, with evidence that symptomatic improvements attributable to ranolazine are not offset by increased mortality. 75 On this ground, together with the fact that comparative trials have failed to show whether ranolazine has a clear-cut impact on mortality, the efficacy of ranolazine in the prevention of angina attacks needs to be reassessed by further studies.…”
Section: -60mentioning
confidence: 99%